Perfil epidemiológico e manifestações clínicas e laboratoriais dos acidentes escorpiônicos atendidos em hospital de referência do Tocantins - Rossi, Alexsandra (2020)
The importance of accidents involving contact with scorpions can be expressed by their high incidence and potential to cause cases of severe poisoning. These accidents are recognized by the World Health Organization (WHO) as an emerging public health problem that is sometimes overlooked. The objective of the study was to analyze the cases of accidents caused by scorpions treated at the Hospital de Tr disease Tropical, located in the municipality of Araguaína, in the north of the state of Tocantins, from April to November 2019. This is an observational, descriptive study with a quantitative and qualitative approach. During the period evaluated, 534 accidents involving venomous animals were reported and of these 138 (25.8%) of the cases were due to scorpions. Of the 113 patients evaluated, most were adults with no difference between genders in the urban area (73.2%), from Araguaína-TO (76,99%), with the presence of debris close to home in 62.5%. Scorpionic accidents were mostly mild (84.07%), in the upper limbs (63.83%), with pain at the bite site (95%), starting in the first 15 minutes and considered moderate to high intensity by 72 , 32% of the injured. Other local symptoms were edema (68.14%), erythema (74.34%) and local paresthesia or radiating to the entire affected limb (38%). Anti-scorpion serum was used in 15.04% of the cases treated, corroborating the frequency of moderate / severe cases (15.93%). The presence of two paresthesia-like neurological manifestations has been described: perioral paresthesia and tongue paresthesia. Perioral paresthesia is associated with females (OR= 3,36) and the presence of tachycardia (OR=4,58). Only 12.77% of patients who underwent laboratory tests showed changes. The specimens identified were: Tityus confluens, Tityus aff. matogrossensis and Jaguajir agamemnon, which are animals described in the State of Tocantins. They are species reported for the state of Tocantins and described for areas of cerrado and transition between savannas and Amazon rainforest. The epidemiological profile reinforces the need for continuous training of health professionals involved in the diagnosis and treatment of the injured, aiming, in a timely manner, to identify the gender of the offending scorpion and the clinical classification of the case to institute appropriate treatment. The strengthening of the assistance area is essential to reduce the lethality of the disease, especially in the most vulnerable groups.